Cycle Highways: a new concept of infrastructure - Dias, G. J. C. (2021)
Only 8% of the European Union residents use a bicycle to commute, being the Netherlands being the country with the biggest representativeness in bicycle use for everyday activities. The advent of e-bikes brought more people to use bicycles, especially elderly or people with reduced mobility. This technology also allowed people to travel longer distances, which is a key factor for the implementation of Cycle Highways (CH). These facilities were thought to be the bicycle connections between cities where people need to travel to work or study. CH are longer than 5?km and allow cyclists to perform higher speeds than those practiced in cities. They can be placed alongside highways or in totally different sites, but the basic requirement is that bicycles have their own space away from cars and pedestrians to make inter-city journeys. This article presents the concept of this type of infrastructure, some successful examples in the Netherlands, Denmark, Germany, and the United Kingdom, and the technical information from two Danish manuals, which can be consulted when planning and implementing Cycle Highways to connect people and places.